The emergence of non-infectious epiglottitis after the era of Hemophilus influenza type B universal vaccination: two case reports and literature review - Safia, Alaa; Shehadeh, Rabie; Merchavy, Shlomo (Frontiers in Pediatrics, 2024)
Objective: Following the global dissemination of vaccination protocols for Hemophilus influenza type b, the occurrence rate and burden of infectious epiglottitis decreased rapidly and substantially. However, this gave space to the rise of non-infectious causes, with children being more vulnerable than adults. This report aims to divert the clinician's attention to the existence of other non-infectious causes of epiglottitis, all of which require careful attention and timely management for favorable clinical outcomes.Case summary: Two cases with positive vaccination history were encountered in our practice. The first case was a 4-year-old girl, presenting with stridor drooling, and dyspnea, later complication by apnea. The fiberoptic exam revealed severe epiglottitic swelling with near-complete injury of the vocal cords with a circumferential burn. She did not respond to racemic epinephrine, and a tracheostomy was done. She was discharged after 6 days with minimal soft palate swelling. The second case was a 2-year-old boy presenting after exposure to an alkaline solution. The case exhibited similar symptoms but with white plaques and edema of the soft palate. The fiberoptic exam showed swelling and erythema of the supraglottic structures with partial obstruction. Although the blood culture was negative, he was intubated and given four intravenous boluses of dexamethasone and penicillin. On the fifth day, the patient was discharged after a normal fiberoptic examination.Discussion: These cases highlight a crucial shift in the etiology of epiglottitis post widespread Hemophilus influenza type b vaccination, underscoring the emergence of non-infectious causes, particularly in children. The two cases presented, both with vaccination histories, demonstrate diverse non-infectious triggers leading to severe epiglottitis. The first case, involving thermal injury, and the second, chemical exposure, both necessitated intensive interventions, including tracheostomy and intubation. These instances emphasize the need for heightened clinical vigilance for non-infectious epiglottitis, demanding prompt recognition and management to ensure positive outcomes. This shift in etiology calls for a reevaluation of traditional diagnostic and therapeutic approaches to pediatric epiglottitis.